KEDUDUKAN BARANG BUKTI SITAAN TINDAK PIDANA KORUPSI DI TINJAU DARI ASPEK KEPERDATAAN - Juanda Sitorus (JOURNAL EQUITABLE, 2020)
Position of Evidence Confiscated Corruption Crime in Review of Civil Aspects that in the mechanism of seizure of assets through criminal law, in principle the position of third parties is those parties other than the perpetrators / intellectuals of a corruption case, and related to confiscation aimed at assets that have been transferred ownership to a third party then if the assets are seized from a third party, the third party concerned must prove that the acquisition of the asset is based on the acquisition of good faith. Implementation of Asset Seizure from Transferred Corruption Results Ownership of Third Parties that seizure of objects related to a criminal act of corruption has become a legal requirement in order to uphold law and justice, so that the act of seizing assets resulting from a crime committed against assets belonging to the perpetrators of crime Upun assets that have switched ownership to third parties are very urgent, considering that aside from the need for evidence at the trial, the evidence that is confiscated is also intended to recover state financial losses resulting from corruptionthe criminal acts of corruption he did together with other actors.